Implementasi Algoritma K-Means dalam Analisis Klasterisasi Penyebaran Penyakit Hiv/Aids - Tita Puspita Sari; April Lia Hananto; Elfina Novalia; Tukino Tukino; Shofa Shofia Hilabi (Fakultas Teknik Universitas Hamzanwadi, 2023)
The most crucial component of everyone's life is their health, especially for young people, health problems that often arise in the younger generation are promiscuity or free sex. HIV/AIDS cases were reported in the last 30 years, from 1992 to 2022 as many as 2,052 were infected with HIV/AIDS. Dozens of them are students and college students. This study's objective was to cluster the total cases of HIV/AIDS based on sub-districts in Karawang district. Seeing which areas need more attention in dealing with cases of HIV/AIDS transmission and the areas with the highest cases can serve as a manual for choosing the highest areas and these areas can be the main focus. The approach adopted for this study is data mining. To solve the existing problems, the authors use the K-Means algorithm using 4 clusters to find out which sub-district groups have very high, high, medium and low numbers of HIV/AIDS cases by calcualating the centroid/mean of the cluster data. The results of the study contained 4 clusters as follows: cluster 0 with low criteria earned 73%, cluster 1 with very high criteria earned 3%, cluster 2 with medium criteria earned 7%, and cluster 3 with high criteria earned 17%.